2023
DOI: 10.1055/a-2081-4599
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Lipid Profile Between Subclinical Hypothyroidism and Well-Matched Controls: A Meta-Analysis

Abstract: In previous studies, subclinical hypothyroidism (SCH) has been associated with altered lipid profiles. However, since the discrepancy between these study results may reside in the great heterogeneity of the populations studied, this relationship is controversial. This study aimed to explore the changes in total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-c), and high-density lipoprotein cholesterol (HDL-c) between subclinical hypothyroidism (SCH) and well-matched euthyroid (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The greater impact of higher TSH values with respect to producing a more adverse lipid profile is in keeping with the finding that there is an increased risk of coronary heart disease events and mortality in those with greater TSH elevations, especially greater than 10 mIU/L [21]. The same meta-analysis [14] found greater differences in the TC, LDL-C and HDL-C compared with the euthyroid group in patients with subclinical hypothyroidism when comparing those aged between 21 and 55 years of age. Regarding sex, the increases in LDL-C and decreases in HDL-C were seen regardless of the percentage of women in the group being studied.…”
Section: Subgroup Analysessupporting
confidence: 64%
See 4 more Smart Citations
“…The greater impact of higher TSH values with respect to producing a more adverse lipid profile is in keeping with the finding that there is an increased risk of coronary heart disease events and mortality in those with greater TSH elevations, especially greater than 10 mIU/L [21]. The same meta-analysis [14] found greater differences in the TC, LDL-C and HDL-C compared with the euthyroid group in patients with subclinical hypothyroidism when comparing those aged between 21 and 55 years of age. Regarding sex, the increases in LDL-C and decreases in HDL-C were seen regardless of the percentage of women in the group being studied.…”
Section: Subgroup Analysessupporting
confidence: 64%
“…Some studies have also conducted various subgroup analyses of effects on the lipid profile, including differences based on study location, degree of TSH elevation, age, sex, and body mass index. Examining the impact of degree of TSH elevation on lipid alterations in the recent metaanalysis [14], it was found that elevations in LDL-C, TC, and TG were greater in subgroup of patients with subclinical hypothyroidism and with TSH values greater than 10 mIU/L than in those with TSH values less than 10 mIU/ L. However, this did not apply to the degree of decrease in HDL-C values. The greater impact of higher TSH values with respect to producing a more adverse lipid profile is in keeping with the finding that there is an increased risk of coronary heart disease events and mortality in those with greater TSH elevations, especially greater than 10 mIU/L [21].…”
Section: Subgroup Analysesmentioning
confidence: 98%
See 3 more Smart Citations